Social Media Marketing : an Hour a Day. - Evans, Dave (John Wiley & Sons, 2012)
Updated with 100 pages of new content, this edition is better than everIn the newest edition of his top-selling book, social media expert Dave Evans bypasses theory to provide you with practical, hands-on advice on developing, implementing, and measuring social media marketing campaigns. In what can be an overwhelming topic, he demystifies the jargon, dispels the myths, and helps you develop an effective, day-by-day plan. Revised and updated with more than 100 pages of new material on all the latest developments, Evans includes new and updated coverage on Facebook, Twitter, and Google+; the lat.